Answers

The Brainliest Answer!
2016-02-07T09:30:45+05:30
f + s = 45
(f-5)(s-5)=4(f-5)
----
Substitute for "f" and solve for "s":
f = 45-s
(45-s-5)(s-5) = 4(45-s-5)
----
Divide both sides by 45-s-5 to get:
s-5 = 4
s = 9 (son's age now)
----
Solve for "f":
f+9 = 45
f = 36 (father's age now)
2 5 2
na can't get
can u c comments,report,rating,thanks, etc
yes
its only when 2 ppl answer the question.
u can mark now :)
2016-02-07T10:12:37+05:30
Let the father's and son's age be x and y respectively.
From the question :
x+y=45.
5yrs ago the product of their ages:
(x-5)(y-5).
it was = 4(x-5).
∴(x-5)(y-5)=4(x-5)
∴y-5=4
&y=9
we know that x+y=45.
∴x+9=45
∴x=36.
∴their present ages are:
Father:36yrs.
Son:9yrs.

hope it helps and pls mark this as best answer :)

0